2022
DOI: 10.1002/jclp.23359
|View full text |Cite
|
Sign up to set email alerts
|

Daily associations of interpersonal and emotional experiences following stressful events among young adults with and without nonsuicidal self‐injury

Abstract: Objectives Emotional and interpersonal dysfunction appears central to nonsuicidal self‐injury (NSSI), yet research examining the interplay of these factors among individuals with NSSI is limited. This study aimed to specify such associations before and after daily stressful events among individuals with (vs. without) NSSI. Methods Young adult participants (Mage = 20.4) with past‐year (n = 56) or no history (n = 47) of NSSI completed daily diary assessments over a 2‐week period. Results No differences in rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…For example, dialectical behavior therapy used for adolescents involved improving emotion regulation and establishing effective interpersonal relationships [88][89][90][91] , yet it did not encompass the content of improving interpersonal emotion regulation strategies. Most of the research on interpersonal emotion regulation strategies was exploratory 82,86 . Thus, further research is needed to explore the application of interpersonal emotion regulation methods and their intervention effect on improving interpersonal emotion regulation ability and multidimensional social functioning; and reducing NSSI behaviors and suicidal ideation.…”
Section: Interpersonal Emotion Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, dialectical behavior therapy used for adolescents involved improving emotion regulation and establishing effective interpersonal relationships [88][89][90][91] , yet it did not encompass the content of improving interpersonal emotion regulation strategies. Most of the research on interpersonal emotion regulation strategies was exploratory 82,86 . Thus, further research is needed to explore the application of interpersonal emotion regulation methods and their intervention effect on improving interpersonal emotion regulation ability and multidimensional social functioning; and reducing NSSI behaviors and suicidal ideation.…”
Section: Interpersonal Emotion Regulationmentioning
confidence: 99%
“…Individuals with borderline personality disorder tendencies had more prominent issues with interpersonal conflict behaviors (eg, arguing, hitting, and throwing things) and difficulties with emotion regulation 85 . A study of individuals engaged in NSSI showed that a positive interpersonal experience after a stressful event was related to lower negative emotional responses, highlighting the potential relevance of interpersonal emotion regulation to the NSSI population 86 . Several psychotherapeutic interventions specifically developed for NSSI in adolescence demonstrated small to moderate effects to reduce NSSI and improve anxious and depressive symptoms 79 .…”
Section: Application Of Emotion Regulation Strategies In Nonsuicidal ...mentioning
confidence: 99%
“…Nonsuicidal self-injury (NSSI), which refers to direct and deliberate destruction or alteration of bodily tissue without lethal intent (e.g., self-cutting, burning) (American Psychiatric Association, 2022), is a particularly prevalent mental health concern among post-secondary students as approximately 17 to 25% of students report lifetime NSSI engagement (Kiekens et al, 2023; Xiao et al, 2017). Students who engage in NSSI report heightened levels of depressive symptoms and perceived stress (Boyne & Hamza, 2022), and greater negative emotional reactions to daily stressful life events (Berghoff et al, 2022), compared to their peers who do not engage in NSSI. Understanding how students with existing NSSI engagement cope with stressors and distress may provide important new insight into the short-term processes that exacerbate more enduring risk later (e.g., heightened engagement in NSSI and associated internalizing symptoms).…”
Section: Introductionmentioning
confidence: 99%
“…e emergence of NFT artwork creation [7] has completely changed the way and experience of artwork creation, making the public a member of real artwork creation [5,8]. An audience with the ability to create artworks can change the performance elements of artworks at any time, which enables the audience not only to have a dialogue with art from the artworks [9], but also to express speci c emotional experiences [10] in speci c artworks [11]. In general, the social participation and timely expression of NFT artworks break through the boundaries of the artist and the work itself, enabling the audience to express their emotions from the work, and unprecedentedly expanding the depth and breadth of artistic expression.…”
Section: Introductionmentioning
confidence: 99%